Analisis Determinan pada Faktor yang Mempengaruhi Minat Nasabah dalam Menggadaikan Emas di Pegadaian UPS Pasar Anom - Khair, Anisatul; Setiawan, Firman (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Sharia pawnshops are the best solution in meeting human needs which are increasingly consumerist amidst the development of the digital world which provides easy access for humans to fulfill their lives. Even though banks also issue pawn products, pawnshops still exist with their pawn products because the process is fast, easy and safe without having to queue longer. So here the researchers are interested in examining what factors influence customers' interest in pawning their gold at Pegadaian UPS Pasar Anom. This research uses quantitative methods with primary data obtained directly through distributing questionnaires to 60 respondents. The analysis technique used is multiple linear regression. The results of the research show that the variables administration costs, estimated value, ijarah costs, and product quality have a positive and significant effect on customer interest because ttable greater than tcount and the significance value is smaller than 0.05. Meanwhile, the late fine variable has a negative and insignificant effect on customer interest, this is proven by ttable smaller than tcount and the significance value is greater than 0.05.